2016
DOI: 10.1002/adfm.201601946
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen‐Bonded Organic Semiconductors as Stable Photoelectrocatalysts for Efficient Hydrogen Peroxide Photosynthesis

Abstract: Research on semiconductor photocatalysts for the conversion of solar energy into chemical fuels has been at the forefront of renewable energy technologies. Water splitting to produce H2 and CO2 reduction to hydrocarbons are the two prominent approaches. A lesser‐known process, the conversion of solar energy into the versatile high‐energy product H2O2 via reduction of O2 has been proposed as an alternative concept. Semiconductor photoelectrodes for the direct photosynthesis of H2O2 from O2 have not been applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
113
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 123 publications
(115 citation statements)
references
References 41 publications
2
113
0
Order By: Relevance
“…The hydrogen-bonded pigment QNC is particularly interesting in the context of biological applications due to reported nontoxicity 46 and presence of NH functional groups that enable direct bioconjugation reactions 47 . Recently QNC, in the form of vacuum-evaporated thin films, has been reported as a promising semiconductor, with outstanding stability, ambipolar charge carrier mobility, and favourable optoelectronic 48 and photocatalytic 49 properties. The multifunctionality and availability of QNC make it a good target for making organic semiconducting hierarchical nanostructures.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrogen-bonded pigment QNC is particularly interesting in the context of biological applications due to reported nontoxicity 46 and presence of NH functional groups that enable direct bioconjugation reactions 47 . Recently QNC, in the form of vacuum-evaporated thin films, has been reported as a promising semiconductor, with outstanding stability, ambipolar charge carrier mobility, and favourable optoelectronic 48 and photocatalytic 49 properties. The multifunctionality and availability of QNC make it a good target for making organic semiconducting hierarchical nanostructures.…”
Section: Resultsmentioning
confidence: 99%
“…It has been recently demonstrated that some organic semiconducting small molecules can act as aqueous photocatalysts 28,29 or photoelectrocatalysts 30,31 32,33 inspiring detailed investigation into the role of eumelanin interactions with reactive oxygen species (ROS). In his 1990 paper, Sarna noted that the molar quantity of H 2 O 2 produced during the photochemical degradation of eumelanin was 20% higher than the molar equivalent of the starting monomers.…”
mentioning
confidence: 99%
“…[14,16] The molecular dye derivatives here, however, generate peroxide more efficiently under neutral to basic pH conditions. Irradiation of solutions without dye does not produce any H 2 O 2 , just as dye solutions in the dark do not produce H 2 O 2 .…”
Section: H 2 O 2 Evolution Experiments With Different Sacrificial Elementioning
confidence: 87%
“…We synthesized three compounds shown in Figure 1b. [16] As a water-soluble analog to the proven photo and electrocatalyst, [14,20] perylenetetracarboxylic-3,4,9,10-diimide (PTCDI), we synthesized a derivative bearing two sulfonic acid-terminated groups: [16] As a water-soluble analog to the proven photo and electrocatalyst, [14,20] perylenetetracarboxylic-3,4,9,10-diimide (PTCDI), we synthesized a derivative bearing two sulfonic acid-terminated groups:…”
Section: Organic Dyes In Water-homogeneous Solutionsmentioning
confidence: 99%
See 1 more Smart Citation